Characterization of the Hydrothermal Alteration around the Björkdal Au Deposit, Skellefte District, Sweden - Erneholm, Madeleine (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2017)
Sixteen samples from 8 locations within and surrounding the Björkdal mine area in northern Sweden were chosen in order to reevaluate and characterize previous interpretations of the lithology and hydrothermal alteration. Geochemical analysis by ICP-MS was made in order to chemically classify the lithology of the area and petrological studies were made by study of thin sections and core logging. Three different sets of major alteration types with similar protolith were noted where two dominated: a) a silicified, sericitic, deformed unit; b) a felspathic altered unit with various intensity of epidote; c) amphibole and a so called green banded unit that has undergone Ca-Mg-metasomatism. The main host rock lithology could be identified as a coarse grained, equigranular, plagioclase and (Na-K)-feldspar dominated rock with slightly elongated, stubby grains that have an interlocked, igneous texture. Apatite is a reoccurring accessory mineral in all samples and remains relatively undamaged. Fragmental quartz occur in the samples and is primary to later forming alteration minerals.Amphiboleis also considered to be primary, but can also been formed during regional metamorphism. Two lithologies could be identified in addition to the main protolith. Two samples were located above the marble horizon and was classified as basaltic unit with Ca-plagioclase, biotite and amphibole. One sample mainly consisted of aligned amphibole and biotite and is considered to be an amphibolite xenolith or a dyke intruding the main protolith rock. An increase in the alteration minerals albite, amphibole, epidote and allanite, with peak intensity found north-east of the mine site. This is confirmed by the geochemistry of major elements Fe2O3, MgO, CaO and the ratio between Na2O and K2O. The zonation is explained by a suggested increase in temperaturecondition during metamorphosis. This could be explained by either an underlying intrusion or bystructurally controlled variation in metamorphism by e.g. major faults running through the ...